Pemulihan Korban Melalui Restitusi Bagi Korban Kekerasan Seksual (Studi Putusan Nomor : 989,PID.SUS/2021/PN BDG) - Madyana, Rida; Faozi, Safik (Universitas Ekasakti, 2023)
The crime of sexual violence is part of a crime against decency, where the act does not occur to adults but also occurs to minors, either directly or indirectly. Legal considerations for imposing restitution for victims of the crime of sexual violence in the Herry Wirawan incident With reference to the problems that have been described, this study aims to examine criminal acts of sexual violence in the Herry Wirawan incident, especially regarding legal considerations in granting restitution to victims and the legal protection that should be given to the victim's children. This research uses normative legal methods with statutory and case approaches. This research is an in-concreto legal research. The results of the study show that the judge's considerations in making decisions are based on the public prosecutor's indictments, the statements of the accused, the statements of witnesses, and evidence. For legal protection for the victim, the defendant is sentenced to death, and the victim's children are entitled to receive compensation or restitution from the defendant. In addition, child victims also receive protection in the form of social rehabilitation and psychosocial assistance during their treatment process until their recovery. Protection and assistance for the victim's children is also provided at every stage of the examination, starting from investigation, prosecution, to trial. This aims to provide comprehensive protection for victims and ensure that their rights are guaranteed during the law enforcement process.